2000
DOI: 10.1007/pl00007936
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism of a human reaction to vibration stress by palmar sweating in relation to autonomic nerve tone

Abstract: The palmar sweating reaction to vibration stress was related to the background level of the autonomic nerve tone. The sweating volume was in direct proportion to the acceleration magnitude of vibration. The reaction of palmar sweating to vibration stress may be mediated through both the adrenergic and cholinergic fibers of the autonomic nervous system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 6 publications
1
7
0
Order By: Relevance
“…We have earlier shown that vibration at 125 Hz with a magnitude of 50 m/s 2 rms, unweighted (equivalent to 6.25 m/s 2 rms weighted), induces palmar sweating response to vibration exposure in the contralateral side (5). In our present study, on the other hand, we observed that even a smaller magnitude of vibration produces a palmar sweating response.…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…We have earlier shown that vibration at 125 Hz with a magnitude of 50 m/s 2 rms, unweighted (equivalent to 6.25 m/s 2 rms weighted), induces palmar sweating response to vibration exposure in the contralateral side (5). In our present study, on the other hand, we observed that even a smaller magnitude of vibration produces a palmar sweating response.…”
Section: Discussionsupporting
confidence: 45%
“…In an earlier experimental study, we found that the higher the vibration intensity, the larger the palmar sweating response to vibration stress (5). The aim of our present study was to elucidate the effects of vibration frequency on palmar sweating response.…”
mentioning
confidence: 81%
“…In earlier experimental studies, we observed a marked palmar sweating response during such forms of physical stress as exposure to cold ambient temperatures and hand-arm vibration (4,5). Exposure to noise was also observed to induce a palmar sweating response (6).…”
mentioning
confidence: 78%
“…Measurements paper (Ando et al 2000). A capsule of 1 cm 2 in size was mounted on the right palm, through which dry N 2 gas flowed.…”
Section: Subjectsmentioning
confidence: 99%
“…Palmar hyperhidrosis is one of the signs often encountered among patients with hand-arm vibration syndrome, which is an occupational disease that results from the long-term use of vibratory tools (Matoba et al 1977). It has been shown that vibration or noise stimuli make palmar sweating increase (Ando et al 2000;Sakakibara et al 1989). The combined effects of vibration and noise on palmar sweating have also been observed among healthy subjects (Sakakibara et al 1989).…”
Section: Introductionmentioning
confidence: 96%